PENGARUH LAMA FERMENTASI TERHADAP KARAKTERISTIK MINUMAN PROBIOTIK KULIT NANAS MADU - Rifatul Masrikhiyah; Widia Pangestika; Ratu Diah Koerniawati (Program Studi Ilmu Teknologi Pangan Universitas Muhadi Setiabudi, 2026)
Nutritional deficiencies in Indonesia necessitate functional food innovations that support gastrointestinal health. Pineapple peel has significant potential as a fermentation substrate due to its high carbohydrate content, yet its utilization remains sub-optimal. This study aimed to determine the optimal formulation and fermentation duration of a probiotic beverage based on pineapple peel and honey. Analytical methods included hedonic and quality hedonic testing by 25 semi-trained panelists, and theoretical nutritional estimation using NutriSurvey 2007. The results indicated that a 2-day fermentation period (P1) produced the most stable physical and sensory characteristics. Formulation P1 achieved the highest overall acceptability score of 3.74 on a 1–5 hedonic scale, with a taste score of 3.86 and texture score of 4.02. The theoretical nutritional profile per serving yielded 203.4 kcal of energy and 53.3 g of carbohydrates. In conclusion, controlling the fermentation duration to 2 days is a critical parameter for producing an acceptable probiotic beverage. This study is crucial for advancing the utilization of agricultural by-products as local food-based nutritional intervention products.